(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Evaluation of left ventricular function after CRT implantation. Subjects and research methods: The design of a comparative clinical trial before and after the intervention was carried out on 33 patients with heart failure who were implanted with CRT at Bach Mai Hospital. Patients were evaluated for electrocardiogram, myocardial tension before CRT insertion and after 1, 3 months and described clinical and laboratory features. Results: The study showed that the QRS interval improved statistically at the time of follow-up while the PQ interval improved later at 1 month and 3 months after implantation. Regarding left ventricular systolic function, left ventricular end-systolic volume decreased statistically, and left ventricular ejection fraction increased statistically at the time points after CRT implantation. The total left ventricular longitudinal strain (GLS) also increased statistically significantly at the time of follow-up after intervention. Conclusion: Left ventricular function was significantly improved after CRT implantation in patients with severe heart failure.